2021
DOI: 10.1093/ofid/ofaa651
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Clinical Outcomes Using Ceftazidime/Avibactam, Ceftolozane/Tazobactam, and Meropenem/Vaborbactam for the Treatment of Multidrug-Resistant Gram-Negative Infections

Abstract: Ceftolozane-tazobactam (C/T), Ceftazidime-avibactam (C/A), and Meropenem/vaborbactam (M/V) are new beta-lactam/beta-lactamase combination antibiotics commonly used to treat multi-drug resistant Pseudomonas aeruginosa (MDRPA) and carbapenem-resistant Enterobacteriaceae (CRE) infections. This review reports the clinical success rates for C/T, C/A., and M/V. PubMed and EMBASE were searched from January 1 st, 2012 through September 2 nd, 2020 for publications detailing use of C/T, C/A, and M/V. Meta-analysis deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…8 A meta-analysis that evaluated the use of ceftazidime-avibactam in patients with MDR gram-negative infections found the pooled clinical success rate to be 73.3%, similar to polymyxins (66%-79%). 9 This study had several limitations. Therapies included in this study could have been used for different organisms, which may have overestimated true utilization rates of these antibiotics for CRE.…”
Section: Discussionmentioning
confidence: 93%
“…8 A meta-analysis that evaluated the use of ceftazidime-avibactam in patients with MDR gram-negative infections found the pooled clinical success rate to be 73.3%, similar to polymyxins (66%-79%). 9 This study had several limitations. Therapies included in this study could have been used for different organisms, which may have overestimated true utilization rates of these antibiotics for CRE.…”
Section: Discussionmentioning
confidence: 93%
“…A meta-analysis of 29 studies evaluating C/T, C/A, and M/V, the pooled clinical success rates for those antibiotics was 73.3% (95% CI, 68.9%-77.5%). 39 However, that analysis did not include studies with a comparator group and therefore could not analyze the performance of the new combination antibiotics compared to older therapies. 39 Additionally, the clinical effectiveness of I/R was not included in that analysis.…”
Section: Discussionmentioning
confidence: 99%
“…39 However, that analysis did not include studies with a comparator group and therefore could not analyze the performance of the new combination antibiotics compared to older therapies. 39 Additionally, the clinical effectiveness of I/R was not included in that analysis. A review of MDRGNO bloodstream infections found a decrease in 30-day mortality associated with C/A use.…”
Section: Discussionmentioning
confidence: 99%
“…The triazole-based anticancer agent [13] carboxyamidotriazole (CAI) 2 is under clinical trials (Phase III). Cefatrizine 3 and tazobactam 4 are among the most prescribed antibiotics; [14] tert-butyldimethylsilyl-spiroaminooxathioledioxide (TSAO) 5 is potential anti-HIV reverse transcriptase inhibitor. [15] Rufinamide 6, a popular anticonvulsant, is currently used to treat seizure disorder.…”
Section: Introductionmentioning
confidence: 99%